Factors Related to Behavior Handwashing Using Primary-School-Age Children's Soap on Rt's Covid-19 Pandemic. 008/Rw. 007 Bananas, Ciputat Timur in 2021 - Leandra Binar Ilyasa; Andriyani Asmuni; Nur Romdhona; Ernyasih Ernyasih (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
About 40% of the world's human population has no place in their homes to wash their hands with soap and water. The prevalence of handwashing behavior with soap for school children in Indonesia in 2018 was 46%. In 2018 the behavior of washing hands with soap in Banten Province in the group of school children was 44.5%. South Tangerang City has a prevalence of handwashing behavior with soap in school children in 2018 of 69.12%. This research was conducted to Factors Related to the Behavior of Washing Hands with Soap for Elementary School Age Children During the COVID-19 Pandemic at RT.008/RW.007 Pisangan, East Ciputat in 2021. Cross-sectional study design with 86 people as samples, the sampling done by total sampling technique. Data analysis used chi-square test (α = 0.05). Variables related to the handwashing behavior with soap are knowledge (p-value 0,038. OR= 3,4), facilities (p-value = 0,000. OR= 76,3), the role of parents (p-value = 0,005. OR= 4,5). While variables not related to handwashing behavior with soap are attitude (p-value = 0,132. OR = 8,1). Factors Related to the Behavior of Washing Hands with Soap at RT.008 RW.007 Pisangan, East Ciputat are knowledge, facilities, the role of parents. An active parental role is needed so that they can guide, teach and be an example for their children in good handwashing behavior with soap. There is a need for prevention actions such as the distribution of handwashing soap and pamphlets containing an invitation to wash hands and this activity is under the supervision of the Pisangan Health Center